Macrophages in osteoporotic fractures: from immunometabolic mechanisms to precision therapeutic approaches - Xing, Jiahui; Li, Haibo; Xia, Honggang; Xia, Lilei; Zhao, Hongzhou (Frontiers in Endocrinology, 2025)
Osteoporosis (OP) is a systemic bone disease characterized by reduced bone mass and deterioration of bone microarchitecture. Its critical complication, osteoporotic fractures (OPF), imposes a significant global disease burden. Macrophages, serving as central regulators within the osteoimmune microenvironment, dynamically modulate bone homeostasis and fracture healing through polarization (into pro-inflammatory M1 and reparative M2 phenotypes) and metabolic reprogramming. In OPF, OP-inducing factors (such as estrogen deficiency and aging) induce metabolic dysregulation in macrophages by disrupting the balance between glycolysis and oxidative phosphorylation (OXPHOS), causing aberrant succinate accumulation, and depleting NAD+ levels. This dysregulation disrupts the orderly transition from pro-inflammatory M1 to reparative M2 polarization, ultimately leading to insufficient inflammatory initiation in the early fracture phase and impaired osteogenic differentiation during later stages. Targeting this mechanism, innovative therapeutic strategies centered on macrophage metabolic reprogramming and polarization modulation are rapidly developing. These include nanocarriers for mitochondrial function restoration, bioactive coatings enabling time-programmed osseointegration, immunomodulatory smart hydrogels, and functionalized composite biomaterials. These strategies effectively promote osteoporotic bone regeneration by synergistically optimizing osteoimmune homeostasis and the osteoblast-osteoclast balance. This review systematically summarizes the immunometabolic mechanisms of macrophages in OPF and explores targeted intervention strategies, providing novel perspectives for the precision treatment of OPF.